(untitled) - O'Hara, Francis (Cambridge, U.K., 2002)
This fifteen-unit course is ideal for both in-service and pre-service students. It deals with the many situations in which hotel employees meet guests, including reception, restaurant and bar work, answering the phone, giving directions, dealing with guests? problems, writing short e-mails and letters, suggesting places to visit and explaining how things work.
Keywords: English language; Textbooks for foreign speakers